(untitled) (South Asian Journal of Agriculture, 2025)
Farmer awareness is critical for the safe and effective use of agricultural inputs, particularly chemical fertilizers and pesticides. This study assesses the level of awareness among paddy farmers in Batiaghata and Dacope upazilas of Khulna District, focusing on three key dimensions: knowledge of proper application, understanding of health and environmental risks, and adoption of safe practices. A mixed-methods approach was employed, combining quantitative surveys with qualitative key informant interviews (KII). Data were collected from 400 farmers using structured questionnaires, along with in-depth interviews of three agricultural extension officers and three agrochemical sellers from each upazila. Findings reveal that a majority of farmers lack formal training and possess limited knowledge about safe application methods, timing, and crop-specific dosage. Approximately 86% and 90% of respondents reported receiving no training on fertilizer and pesticide usage, respectively. Awareness of the environmental and health consequences of excessive use was also low, particularly in Dacope, where frequent flooding may divert focus from long-term sustainability. Notably, 94% of farmers were unaware of banned pesticides. Batiaghata farmers exhibited significantly higher awareness levels, likely due to better access to extension services. The study also highlights the limited reach of agricultural extension programs and the dominant role of input sellers in influencing farmers’ decisions. While sellers often provide advice, interviews suggest that recommendations may prioritize commercial interests over safety. This underscores the need for improved regulatory oversight and more robust, targeted extension services. The results indicate an urgent need for coordinated awareness initiatives by government bodies, NGOs, and mass media. Context-specific training and consistent information dissemination especially in vulnerable coastal areas—can enhance farmers’ awareness and promote more sustainable agricultural practices. South Asian J. Agric., Vol. 11, No.1, 2025: 45-56